A new species of Odontoglossum (Orchidaceae: oncidiinae) from Ecuador - Dalström, Stig (Universidad de Costa Rica, 2013)
A new and horticultural desirable species of Odontoglossum from Ecuador is described, illustrated and compared with similar species.